2008
DOI: 10.1542/peds.2007-1066
|View full text |Cite
|
Sign up to set email alerts
|

Inattention, Hyperactivity, and School Performance in a Population of School-Age Children With Complex Congenital Heart Disease

Abstract: In this cohort of children with complex congenital heart disease, a significant proportion of the children were at risk for inattention and hyperactivity, and nearly half were using remedial school services. We did not identify any perioperative risk factors, which correlated with high-risk scores or the use of remedial school services. Ongoing neurodevelopmental follow-up and screening are recommended in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
225
2
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 301 publications
(250 citation statements)
references
References 53 publications
14
225
2
9
Order By: Relevance
“…Our results are also in agreement with Shillingford et al. (2008) who demonstrated higher prevalence of ADHD in school‐aged (5–10 years old) children with CHD. Interestingly, as was the case in our study, this higher prevalence was more pronounced using the parent‐report scores as compared with the teacher‐report scores.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our results are also in agreement with Shillingford et al. (2008) who demonstrated higher prevalence of ADHD in school‐aged (5–10 years old) children with CHD. Interestingly, as was the case in our study, this higher prevalence was more pronounced using the parent‐report scores as compared with the teacher‐report scores.…”
Section: Discussionmentioning
confidence: 96%
“…Since children with CHD have greater likelihood of ADHD (Shillingford et al. 2008), we hypothesized that differences in brain structural topology may underlie this diagnosis as well. The risk for ADHD children with complex CHD may, in fact, be 3–4 times higher as in the general population (Shillingford et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear whether the association is due to structural anomalies being physiologically related to neurological deficits [32], enhanced medical surveillance, intervention procedures and/or hospitalizations [33]. Learning disabilities in our study population were indicated by a specific set of FCCs which usually meant that the subject also had a mild neurological deficit such as an incoordination which has also been suggested by other authors [34].…”
Section: Discussionmentioning
confidence: 56%
“…Yet these infants remain subject to considerable perioperative morbidity; including bleeding, organ dysfunction, prolonged mechanical ventilation, and long hospitalizations. These events increase the risk of adverse long-term outcomes (neurodevelopmental dysfunction) of the repair of such defects and result in significant resource utilization and increased health care costs [1,2]. Unfortunately, the currently recognized factors associated with an increased risk of these morbid events, such as prematurity, low birth weight, complexity of the congenital heart defect, genetic syndromes, and extracardiac congenital anomalies, can often not be modified [3].…”
Section: Invited Commentarymentioning
confidence: 99%